Severity of coeliac disease and clinical management study when using a non-metabolised medication: a phase I pharmacokinetic study. Issue 2 (24th February 2023) - Chretien, Marc L; Bailey, David G; Asher, Linda; Parfitt, Jeremy; Driman, David; Gregor, Jamie; Dresser, George K
Abstract : Objective: The non-metabolised antihistamine fexofenadine has oral absorption resulting from transporter activity. Uptake by enterocyte organic anion transporting polypeptides and efflux by an ATP-binding cassette transporter (P-glycoprotein) are primary determinants. Coeliac disease-mediated lesions to the small intestinal mucosa may alter oral absorption of the drug probe, fexofenadine. Design: A phase I, open-label, single-dose, pharmacokinetic study Setting: London, Ontario, Canada Participants: Patients with coeliac disease (n=41) with positive serology and healthy individuals (n=48). Main outcome measures: Patients with coeliac disease—duodenal histology and oral fexofenadine pharmacokinetics within a 3-week period. Healthy individuals—oral fexofenadine pharmacokinetics with water and grapefruit juice. Results: Patients with coeliac disease were stratified by disease severity: Group A (n=15, normal), B+C (n=14, intraepithelial lymphocytosis with/without mild villous blunting) and D (n=12, moderate to severe villous blunting). Patients with coeliac disease in groups A, B+C and D and healthy individuals receiving water had similar fexofenadine AUC0–8 (2038±304, 2259±367, 2128±410, 1954±138 ng.h/mL; p>0.05; mean±SEM) and Cmax (440±73, 513±96, 523±104, 453±32 ng/mL; p>0.05), respectively. These four groups all had higher fexofenadine AUC0–8 (1063±59; p<0.01) and Cmax (253±18; p<0.05) compared with those for healthy individuals receiving grapefruit juice. Coeliac groups had a positive linear trend between disease severity and fexofenadine Tmax (2.0±0.3, 2.7±0.4, 3.1±0.5 hours; p<0.05). Conclusions: Coeliac disease severity based on duodenal histopathology did not affect oral fexofenadine bioavailability. Increased Tmax suggested absorption distal to the duodenum (jejunum + ileum), where histology seems more normal which may be the key determinant. Patients with coeliac disease may not require consideration for alternative clinical drug management for a number of non-metabolised and transport-mediated medications.